2021
DOI: 10.3389/fonc.2021.640804
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Metastatic and Non-Metastatic Thoracic Lymph Nodes in Lung Cancer Patients Based on Dielectric Properties Using Adaptive Probabilistic Neural Networks

Abstract: ObjectiveDielectric properties can be used in normal and malignant tissue identification, which requires an effective classifier because of the high throughput nature of the data. With easy training and fast convergence, probabilistic neural networks (PNNs) are widely applied in pattern classification problems. This study aims to propose a classifier to identify metastatic and non-metastatic thoracic lymph nodes in lung cancer patients based on dielectric properties.MethodsThe dielectric properties (permittivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Choi et al (7) measured the dielectric properties of breast cancer tissue from 0.5 to 30 GHz and demonstrated that both malignant LNs and breast cancer tissue clearly differ from benign tissues. Our previous retrospective study showed that the dielectric property measurements of malignant LNs were higher than those of benign LNs in the frequency range of 1-4,000 MHz (9,10).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Choi et al (7) measured the dielectric properties of breast cancer tissue from 0.5 to 30 GHz and demonstrated that both malignant LNs and breast cancer tissue clearly differ from benign tissues. Our previous retrospective study showed that the dielectric property measurements of malignant LNs were higher than those of benign LNs in the frequency range of 1-4,000 MHz (9,10).…”
Section: Introductionmentioning
confidence: 94%
“…Although the dielectric properties of a variety of physical structures and tissues, including malignant and benign tissues, have been reported by several studies (5)(6)(7)(8)(10)(11)(12)(13), there is still a paucity of data regarding the specific efficacy of these parameters in the classification of pulmonary LN metastasis. Therefore, to investigate the efficacy of using permittivity and conductivity to predict pulmonary LN metastasis, the dielectric properties of both benign and malignant pulmonary LNs were examined over a frequency range of 1-4,000 MHz (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In China, Lu et al [41] developed an ML model (XG Boost) combining dielectric properties to assess whether thoracic lymph nodes were benign or malignant in patients with non-small cell lung cancer. Traditionally, surgeons use frozen sections to diagnose metastatic lymph nodes, which is time-consuming and expensive.…”
Section: Lungsmentioning
confidence: 99%